THE CORRELATION BETWEEN THE STUDENTS VOCABULARY MASTERY WITH THEIR READING COMPREHENSION ABILITY IN LEARNING ENGLISH AT SMPIT AJIMUTU GLOBAL INSANI TAMBUN, BEKASI - FAUZAN RAHMATULLAH; YON. A.E; SYAMSI EDI (GANEC SWARA, 2024)
This study aims to identify and analyze the relationship between vocabulary mastery and reading ability in English language learning at SMPIT Ajimutu Global Insani. Good vocabulary mastery is often considered one of the key factors in improving reading ability, as a strong understanding of vocabulary directly impacts students' ability to interpret texts. This study employs a quantitative method with a correlational approach to measure the extent to which vocabulary mastery influences students' reading ability. Data were collected from 20 students through two types of tests: a vocabulary mastery test and a reading ability test. The analysis results reveal a significant positive correlation between vocabulary mastery and students' reading ability, although this correlation falls within the low category. These findings suggest that vocabulary mastery plays an essential role in enhancing reading ability; however, they also highlight the presence of other contributing factors that affect students' reading performance. Based on these results, it is recommended that vocabulary instruction in the English curriculum at the junior high school level be given greater emphasis to enhance students' overall reading ability.